A study on validity of C-reactive protein in deciding the duration of antibiotic therapy in suspected neonatal bacterial infection - Siddaiah, Prashanth; Shetty, Pradeep Nanjappa; N. W., Krishna; Jagadeeshwara, Sowmya (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal septicemia is defined as generalized bacterial infection of newborns documented by positive blood culture in first four weeks of life. Objective of present study was to determine whether C-Reactive protein can be used as a parameter to identify the time point when antibiotic treatment can safely be discontinued in a defined major subgroup of neonates treated for suspected bacterial infection. Methods: A total of 50 neonates with birth weight more than 1500gms with suspected septicemia were enrolled in the prospective study. Serum CRP were determined 24-48 hours after the first dose of antibiotics. If CRP was less than 6mg/l, infants were considered unlikely to be infected and the antibiotic treatment was stopped. If CRP was more than 6mg/l, antibiotics were continued and CRP measured on alternative days in one subgroup (2a) and on seventh day in another subgroup (2b). CRP was the single decision criterion to stop the antibiotic therapy. Negative predictive value with respect to further treatment was determined. Results: Duration of antibiotic therapy could be reduced to less than seven days in 54% cases and < 72 hours in 48% cases. Conclusions: Negative predictive value of serial CRP is 100% in deciding the duration of antibiotic therapy in suspected neonatal septicemia.